Kegagalan Kepulangan Tokoh dalam Cerpen Keluarga dalam Kacamata melalui Lensa Hero’s Journey Campbell - Dedek Wiradi; Adi Suryo Nugroho (Lembaga Yasin AlSys, 2026)
Although Joseph Campbell’s Hero’s Journey framework has been widely used to examine character transformation in literary works, its application to Indonesian digital literature that directly interacts with virtual culture remains relatively limited. This study aims to analyze the inner transformation and failed return of the main character, Kambali, in the digital short story “Keluarga dalam Kacamata” by Artie Ahmad, published on kompas.id, using Campbell’s monomyth framework, which comprises three main stages: departure, initiation, and return. This research employed a descriptive qualitative approach with critical content analysis of the short story text to identify how the stages of the monomyth are presented, inverted, and distorted by the digital context. The analysis shows that Kambali undergoes the Departure and Initiation stages; however, his inner transformation does not culminate in recovery, victory, or a liberating “Ultimate Boon.” Instead, the Virtual Reality glasses generate an illusion of digital happiness that confines Kambali within virtual escapism. The crucial point lies in the failure of the return (“Refusal of the Return”), when Kambali refuses to return to reality and permanently chooses the virtual world as his existential space. The study concludes that Kambali’s narrative deconstructs the conventional hero pattern by affirming the possibility of an ending marked by existential defeat and inner alienation. The short story functions as a sharp critique of the phenomenon of digital disconnect, namely the loss of life’s meaning amid technological advancement that widens the psychological and social isolation gap.